Solidaritas Sosial di Era Post-Modern: Sakralitas Komunitas Salawatan Jaljalut Indonesia - Hefni, Wildani; Ahmadi, Rizqa (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2019)
This study attempts to elucidate the emergence of forms of Islamic spirituality in Indonesian Islam identified as the Jaljalut community of Salawatan. This group has proliferated on Java in the last two decades both in urban and rural areas. This group also has attracted followers from a wide social base to their practices, hence contributing significantly to the improvement of religious performance and social solidarity among Indonesian Muslims. By using Durkheimâ€™s approach of social solidarity and phenominological approach, this paper presents how religious community functions in the integration process, especially in the face of modernity. Social solidarity is the main theme discussed by Durkheim as a moral source for forming social order in society. Conclusions indicated from this study include the proposition that religious community can contribute to integration which is called by Durkheim a collective conscience and collective representations.Keywords: social solidarity, Jaljalut community, modernity.Â Artikel ini menjelaskan munculnya bentuk spritualitas Islam di Indonesia yang direpresentasikan oleh komunitas salawatan Jaljalut. Komunitas ini tumbuh dan berkembang di Jawa baik di daerah perkotaan maupun pedesaan. Komunitas ini diikuti oleh pelbagai kelompok kelas sosial yang kemudian berkontibusi besar dalam pembentukan karakter keberagamaan serta penguatan solidaritas sosial. Dengan menggunakan teori Durkheim tentang solidaritas sosial dan pendekatan fenomenologis, artikel ini mendedah bagaimana komunitas keagamaan salawatan Jaljalut di tengah tantangan modernitas dapat berkontribusi signifikan dalam membentuk kohesi sosial di tengah masyarakat. Solidaritas sosial menjadi tema utama yang dikaji oleh Durkheim sebagai sumber moral untuk membentuk tatanan sosial di masyarakat. Studi ini menegaskan bahwa komunitas keagamaan yang lahir dari solidaritas mekanis dapat berkontribusi pada penguatan integrasi yang disebut oleh Durkheim sebagai nurani kolektif dan representasi kolektif.Kata kunci: solidaritas sosial, komunitas Jaljalut, modernitas.